سيميائية الشخصيات في رواية مررت من خلالي.. ولكن لباسل النادر - إيمان طلاب; رميصاء سليماني; يسرى غنامي (University of El-Oued جامعة الوادي, 2025)
Summary: This research delves into an aspect of narrative construction in the novel، namely the character. The latter is considered the backbone upon which all novels are built. Hence، our study is titled: "The Semiotics of Characters in the Novel 'I Passed Through Me...But' by Bassel Al-Nader،" in which he attempts to show us، through his novel، a moving human experience centered around love، loss، and the decisions that shape our lives. Through this novel، we aimed to uncover the external، internal، and social aspects of the characters present in the narrative text، relying on the semiotic approach. This is because it is an analytical method that grants the researcher freedom in analysis. The study is divided into an introduction، a theoretical first chapter، and a second chapter that integrates the theoretical and the applied، which is a semiotic study of the novel's characters. In the conclusion، we arrived at a set of results، the summary of which is: semiotics is an effective tool in character analysis. It enabled us to deconstruct the semantic and symbolic structures that form the character's identity، thus granting us a deeper understanding of their role within the linguistic fabric.
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: السيمياء- الشخصية- الرواية - مررت من خلالي.. ولكن; Semiotics - Personality - Novel - Passed through me.. But!